Efforts to Increase the Investigative Role of the Boyolali District Police's Satintelkam to Support Satreskrim in Disclosing the Crime of Theft - Richson Artanta Gurning (Advances in Police Science Research Journal, 2022)
The Boyolali Police Satintelkam conducted an investigation to prevent the occurrence of the crime of theft. In the last 3 (three) years, the crime of theft in Boyolali district has increased. This is the duty and responsibility of the police in maintaining and maintaining public security and order in accordance with Law No. 2 of 2002 concerning the National Police of the Republic of Indonesia. Intelligence investigations carried out must be guided by Perkabik Number 1 of 2013 so that the investigation runs according to the existing SOPs. The research was conducted using a qualitative approach, in which researchers went directly to the field to study and explore the phenomena that occurred in the field according to the problems. This research focuses on the investigation of the Boyolali Police Satintelkam. data sources used are primary data and secondary data. Data collection is done through interview, observation and document study techniques. To measure the accuracy of the data, data triangulation was carried out. Then the data analysis technique is carried out through data reduction, data presentation and drawing conclusions. The results of the research that have been obtained indicate that the investigation activities carried out by the Boyolali Police Satintelkam were carried out to support the Satreskrim in disclosing the crime of theft. In carrying out this investigation it is not in accordance with Perkabik No. 1 of 2013. In carrying out the investigation there are still factors that influence both internal and external. Meanwhile, in an effort to increase the investigation carried out through coordination both within the internal and external environment. In the implementation of this coordination, it is expected to be able to find and collect information in accordance with the problem or research objective. The conclusion from the implementation of the Satintelkam investigation of the Boyolali Police is that the investigation has not been carried out optimally because it is not guided by Perkabik No. 1 of 2013 which is an SOP regarding intelligence investigations. coupled with the factors that influence both internally and externally.